2020
DOI: 10.1344/jesb2020.1.j069
|View full text |Cite
|
Sign up to set email alerts
|

Smart specialization for building up a regional innovation agenda: the case of San Luis Potosí, Mexico

Abstract: The state of San Luis Potosí (SLP) is divided into four regions: “Altiplano, Centro, Huasteca and Media”. A large socioeconomic inequality is perceived among the regions, this is especially observed when comparing Centro with the other regions, mainly because Centro region shows greater economic dynamism and has a great amount of companies, educational institutions and research centers, which contributes to lower its socioeconomic lag. In order to reduce the social inequality and the economic development gap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This means that the furniture business has been repositioned from non-based to basic in the future. According to [37] the focus on restoring economic potential in order to become a superior business sector is a difficult thing, but economic dynamism has major advantages, such as the growth in the value of LQ and DLQ of the furniture business.…”
Section: Results Of Research and Discussionmentioning
confidence: 99%
“…This means that the furniture business has been repositioned from non-based to basic in the future. According to [37] the focus on restoring economic potential in order to become a superior business sector is a difficult thing, but economic dynamism has major advantages, such as the growth in the value of LQ and DLQ of the furniture business.…”
Section: Results Of Research and Discussionmentioning
confidence: 99%
“…One of the great current challenges of Micro, Small and Medium Enterprises (MSMEs) is to dynamically innovate to improve their supply of goods, products, and services in order to respond to the changing needs of the market [1,2]. In particular, several studies have concluded that investment in innovation has a high impact on the competitiveness of organizations, which can lead to the introduction of new products and processes.…”
Section: Introductionmentioning
confidence: 99%